2011
DOI: 10.1016/j.ultrasmedbio.2011.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Enhanced rt-PA Thrombolysis in an ex vivo Porcine Carotid Artery Model

Abstract: Ultrasound is known to enhance recombinant tissue plasminogen activator (rt-PA) thrombolysis. In this study, occlusive porcine whole blood clots were placed in flowing plasma within living porcine carotid arteries. Ultrasonically induced stable cavitation was investigated as an adjuvant to rt-PA thrombolysis. Aged, retracted clots were exposed to plasma alone, plasma containing rt-PA (7.1 ± 3.8 μg/mL) or plasma with rt-PA and Definity® ultrasound contrast agent (0.79 ± 0.47 μL/mL) with and without 120-kHz cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
95
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 58 publications
2
95
0
Order By: Relevance
“…A second PCD was aligned confocally with the blood clot sample in flow phantom. This secondary PCD, a focused 2.25-MHz transducer (595516C, Picker Roentgen GmbH, Espelkamp, Germany), has previously been utilized to detect cavitation at 120 kHz (Hitchcock et al, 2011). The PCD aperture is 1.9 cm and the focal length is 5.5 cm.…”
Section: E Ultrasound Exposure and Cavitation Detectionmentioning
confidence: 99%
See 3 more Smart Citations
“…A second PCD was aligned confocally with the blood clot sample in flow phantom. This secondary PCD, a focused 2.25-MHz transducer (595516C, Picker Roentgen GmbH, Espelkamp, Germany), has previously been utilized to detect cavitation at 120 kHz (Hitchcock et al, 2011). The PCD aperture is 1.9 cm and the focal length is 5.5 cm.…”
Section: E Ultrasound Exposure and Cavitation Detectionmentioning
confidence: 99%
“…This finding is consistent with previous investigators using UCAs to nucleate cavitation at 120 kHz. Hitchcock et al (2011) applied continuous-wave 120 kHz ultrasound and Definity V R in an ex vivo porcine carotid artery model. They found that a maximal amount of UH energy was delivered over 30 min at an acoustic pressure of 0.44 MPa (peak to peak).…”
Section: A Comparison Of Uh and Bb Thresholdsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each frequency spectrum was scaled to account for the energy lost due to windowing. A frequency domain comb filter was applied to the power spectrum ( Figure 3C) to extract the ultraharmonic (100 kHz bands at odd multiples of 500 kHz) and broadband 38,39 This process is depicted graphically in Figure 3.…”
Section: Ultrasound Exposure and Cavitation Detectionmentioning
confidence: 99%